Konsep Manajemen Pengelolaan Pendidikan Bermutu di SMK Negeri 1 Tanjung Selor Kabupaten Bulungan Provinsi Kalimantan Utara - Sudarmin Sudarmin; A. Latief Arung Arafah; Siti Patimah; Andi Warisno (Departement of Mathematics Education, 2024)
This examination expects to depict the administration idea of value training the executives in schools. The examination strategy utilized is a subjective enlightening technique, with information assortment procedures through meetings, perception and documentation studies. The examination results show that administration is a course of arranging, coordinating, driving and controlling the endeavors of hierarchical individuals where these four cycles have their separate capabilities to accomplish authoritative objectives. Dakam's endeavors to further develop schools should be possible with three activities: First, making schools better, Second, diminishing the weight. Third, changing over loads into energy. In Regulation no. 20 of 2003 concerning the Public School System Article 4 section 2 peruses: